Monodualistic and Pluralistic Punishment Politics in Criminal Code Reform: Lessons from Indonesia - Mahendra, Januar Rahadian; Emovwodo, Silas Oghenemaro (CV. Ius et Ambientis, 2023)
This research analyzes the problem of punishment in the current Criminal Code because there is a mismatch of socio-political, socio-philosophical, and socio-cultural foundations. This study also analyzes the problems in the current Criminal Code punishment due to the strong retributive influence on punishment so that imprisonment becomes the sole answer for judges in deciding cases. In connection with the various problems of punishment in the Criminal Code, efforts are made to reform the Criminal Code, which is adjusted to the socio-political, socio-philosophical, and socio-cultural foundations so that the reform of the Criminal Code has a mono-dualistic and pluralistic nature. The purpose of this research is to find how the concepts of mono-dualistic and pluralistic influence the reformation of the Criminal Code as well as the political direction of punishment in the reformation of the Criminal Code. Based on the research, the author found that the mono-dualistic and pluralistic nature of the Criminal Code reform influences the material expansion of the principle of legality. In addition, criminal code reform has a contemporary direction that prioritizes not only deterrent effects but also rehabilitative efforts so that it can restore social functions.